A Brief List of Japanese Writings About the Ainu Lands and Russia Until 1799 - V. Yu. Klimov (Russian Japanology Review, 2023)
In 1799, the Russian-American Company (RAC) was founded in Saint Petersburg for the development by Russian merchants and hunters of the Northern Pacific lands. In the same year, Japan’s government made a strategic decision to include the eastern Ainu lands (higashi ezochi), and subsequently the western and northern Ainu lands (nishi ezochi, kita ezochi), into its direct control and to start their economic development. By this year, the Japanese had collected enough information about the Ainu and their lands, about the advance of Russians along the Kuril Islands in the southern direction, about the history of Russia, its emperors, and the Russian language. This article describes Japanese authors and their writings on the mentioned topics, which could not but influence the political decision-making of Japan’s military government (bakufu).